DESCRIPTION OF LAND CONVERSION IN THE ARAL SEA BASIN USING THE TRANSFER MATRIX METHOD - Baytileuova, Guljakhan; Davlatboyeva , Ozoda; Berdimbetova , Amina (Techscience uz - Topical Issues of Technical Sciences, 2025)
An effective approach to quantifying the magnitude and intensity of land cover changes is essential for land use and management decisions. This study uses transfer matrix and intensity analysis to quantify land cover change in the Aral Sea Basin (ASB) from 1995 to 2015. The analysis is based on annual land cover data from the European Space Agency’s Climate Change Initiative and Normalized Density Vegetation Index (NDVI) data provided by the Global Inventory Modeling and Mapping Studies (GIMMS).